1999
DOI: 10.1046/j.1365-2249.1999.01001.x
|View full text |Cite
|
Sign up to set email alerts
|

Galactosylation of serum IgG and autoantibodies in murine models of autoimmune haemolytic anaemia

Abstract: A number of systemic autoimmune diseases are associated with increased levels of the agalactosyl (G0) IgG isoforms that lack a terminal galactose from the CH2 domain oligosaccharide. The current aim was to determine whether the galactosylation of serum IgG is also reduced in a classic antibody-mediated, organ-specific autoimmune condition, and whether the pathogenic autoantibodies are preferentially G0. In two murine forms of autoimmune haemolytic anaemia (AIHA), sera and autoantibodies eluted from erythrocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
4
0
1
Order By: Relevance
“…4,[34][35][36]38,45 It was, therefore, noteworthy that the levels of a particular Th cytokine, IL-17A, and its production by autoreactive T cells, were not only associated with AIHA but correlated significantly with the severity of the disease. There are precedents for factors related to the T-cell response, which could be considered upstream of the production and hemolytic effects of antibodies, influencing the degree of anemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,[34][35][36]38,45 It was, therefore, noteworthy that the levels of a particular Th cytokine, IL-17A, and its production by autoreactive T cells, were not only associated with AIHA but correlated significantly with the severity of the disease. There are precedents for factors related to the T-cell response, which could be considered upstream of the production and hemolytic effects of antibodies, influencing the degree of anemia.…”
Section: Discussionmentioning
confidence: 99%
“…It can be seen from Figure 1 that, while there is a non-significant (P=0.17; Mann-Whitney U test) trend for higher levels of IFN-γ in the sera of patients than in healthy donors, elevated IL-17A concentrations are very strongly associated with the disease (P<0.001). Many factors determine the severity of anemia in AIHA, 4,[34][35][36] but it was also asked whether the levels of either cytokine in the serum of patients were related to their blood hemoglobin levels. Figure 2 demonstrates that there was no clear relationship between concentrations of IFN-γ and hemoglobin, but that IL-17A levels were significantly higher in the more anemic patients, exhibiting a significant inverse correlation with hemoglobin (Rs=-0.49; P=0.034).…”
Section: Interferon-γ and Interleukin-17 Levels In Sera Of Patients Wmentioning
confidence: 99%
“…Lectins are invaluable tools for the study of glycosylation in normal and pathologic conditions, including inflammatory diseases (Tsuchiya et al, 1998). In particular, the sugar epitopes most relevant in inflammatory diseases and aging have been investigated in western blot or enzyme-linked assays using the following lectins: for ␣2,6-linked sialic acid, the lectin from Sambucus nigra (SNA) (Shibuya et al, 1987); for terminal galactose, Ricinus communis (RCA) (Barker et al, 1999;Parekh et al, 1985;Wong et al, 1993) or Erythrina cristagalli (ECL) lectins; for terminal GlcNAc, Bandeiraea simplicifolia II (BSA II) (Alavi et al, 2000;Croce et al, 2007;Sumar et al, 1991) or Psathyrella velutina (PVL) (Tsuchiya et al, 1993); for core fucosylation, Ulex europaeus I (UEA I) (Flogel et al, 1998;Gornik et al, 1999), Aspergillus oryzae (AOL) (Vanhooren et al, 2011) or Lens culinaris agglutinin (LCA) (Shinkawa et al, 2003); for bisecting GlcNAc, Phaseolus vulgaris E4 (PHA-E4) (Shinkawa et al, 2003).…”
Section: Methods Of Glycan Analysismentioning
confidence: 99%
“…It was shown that in vitro reduction of galactosylation enhances the pathogenicity of murine monoclonal IgG1 anti-RBC antibodies injected into mice in a complement-independent way [41]. Studies in several mouse models, however, did not give clear results, since the individual variation was high [42]. In humans, reduced Fc galactosylation of autoantibodies was observed in AIHA.…”
Section: Autoantibody Fc Propertiesmentioning
confidence: 99%